Crystallization characteristics and local grain abnormal growth of amorphous Ge2Sb2Te5 films induced by a Gaussian picosecond laser. (April 2019) - Li, W.Q.; Liu, F.R.; Guo, J.C.; Zhang, Y.Z.; Wang, Y.H.; Liu, F.; Sun, N.X.; Xiao, W.
Highlights: Crystallization characteristics were studied at different laser fluence. Solid-state and liquid-solid phase transitions were found at lower and higher laser fluence, respectively. Abnormal grain growth in the central equiaxed area was observed under higher cooling rate. Morphology and microstructure were obtained of Ge2 Sb2 Te5 film. Abstract: In this paper, crystallization characteristics of amorphous Ge2 Sb2 Te5 (a-GST) films induced by a Gaussian picosecond laser with different laser fluence were carried out using transmission electron microscopy (TEM), Raman spectra and ab initio molecular dynamics (AIMD) simulations. TEM observations presented a solid-state phase transition with nanocrystalline microstructure at lower fluence, while a liquid-solid phase transition accompanied by an ingot-like crystalline microstructure was found at higher fluence, including a central coarse and an outer fine equiaxed regions as well as a columnar crystal region between them. In spite of the remarkable difference in microstructure, the composition of different regions kept constant from the Energy Dispersive Spectrometer (EDS) measurements. Different phase change behavior and laser fluence affected the shift of Raman peaks due to the phase change stress and thermal stress. A laser irradiation coupled AIMD simulation was then developed to study the preferential nucleation possibility. AIMD simulation results indicated that a thermal process in the central coarse equiaxed regions, with a higher cooling rate (10 k/ps) generated by the Gaussian picosecond laser irradiation, reduced the nucleation rate remarkably, causing crystal nucleus have enough space to grow up even to the micrometer scale. This is different from the morphology induced by nano- or femtosecond pulsed laser.